The Impact of Radiologist Screening Mammogram Reading Volume on Performance in the Ontario Breast Screening Program. Issue 2 (May 2022) - Walker, Meghan J.; Hartman, Krystal; Majpruz, Vicky; Leung, Yvonne W.; Fienberg, Samantha; Rabeneck, Linda; Chiarelli, Anna M.
Purpose: Although some studies have shown increasing radiologists' mammography volumes improves performance, there is a lack of evidence specific to digital mammography and breast screening program performance targets. This study evaluates the relationship between digital screening volume and meeting performance targets. Methods: This retrospective cohort study included 493 radiologists in the Ontario Breast Screening Program who interpreted 1, 762, 173 screening mammograms in participants ages 50-90 between 2014 and 2016. Associations between annual screening volume and meeting performance targets for abnormal call rate, positive predictive value (PPV), invasive cancer detection rate (CDR), sensitivity, and specificity were modeled using mixed-effects multivariate logistic regression. Results: Most radiologists read 500-999 (36.7%) or 1, 000-1, 999 (31.0%) screens annually, and 18.5% read ≥2, 000. Radiologists who read ≥2, 000 annually were more likely to meet abnormal call rate (OR = 3.85; 95% CI: 1.17-12.61), PPV (OR = 5.36; 95% CI: 2.53-11.34), invasive CDR (OR = 4.14; 95% CI: 1.50-11.46), and specificity (OR = 4.07; 95% CI: 1.89-8.79) targets versus those who read 100-499 screens. Radiologists reading 1, 000-1, 999 screens annually were more likely to meet PPV (OR = 2.32; 95% CI: 1.22-4.40), invasive CDR (OR = 3.36; 95% CI: 1.49-7.59) and specificity (OR = 2.00; 95% CI: 1.04-3.84) targets versus those who read 100-499 screens. No significant differences were observed for sensitivity. Conclusions: Annual reading volume requirements of 1, 000 in Canada are supported as screening volume above 1, 000 was strongly associated with achieving performance targets for nearly all measures. Increasing the minimum volume to 2, 000 may further reduce the potential limitations of screening due to false positives, leading to improvements in overall breast screening program quality.